The Direction of Industry: A Literature Review on Industry 4.0 - Wichmann, Robert Lawrence; Eisenbart, Boris; Gericke, Kilian (Proceedings of the International Design Society, 2019)
With the rapid success of the digital enterprises in the 21st Century, industrial manufacturing is expected to be approaching the fourth industrial revolution, coined Industry 4.0 (I4.0). The instrumental technology that will drive this evolution is the integration of the physical and digital factory into one cyber physical system. There is consensus among academics and industry alike that there will be an integral paradigm shift in how offerings will be developed and manufactured. While there is much confidence that the future factory will have unprecedented capabilities to satisfy complex customer demands, there is little agreement on how individual organisations can utilise these trends. This paper presents a literature review identifying reoccurring themes and trends of I4.0 and their expected effect on future manufacturing. Central characteristics, challenges and opportunities are identified and discussed. The findings can provide support in developing actionable strategies for industry to direct I4.0 endeavours.